Factors influencing software piracy among students: a case in UiTM Shah Alam / Intan Diyana Azhar - Azhar, Intan Diyana (2007)
Software piracy defined as making unauthorized copies of software by individuals or businesses for resale or to use in workplace, school or home, is an imethical and illegal behaviour pervading today's society. The widespread development of computer processing, the internet and telecommunication in general has led to what we know as the digital environment, a context that has meant a drastic change in the condition of access, distribution and use of intellectual works. Nowadays, it is possible to gain access to digital works almost instantaneously from any place and at any time. In a global environment where the intellectual property is often used without authorization, businesses and economies have been focusing on taking steps to minimize such acts. The software industry has faced unauthorized use in the last couple of decades. As a result, businesses that produce software are looking for new ways to curb any form of unauthorized usage through education and legal means. This research is based on Azjen's Theory of Reasoned Action in order to determine factors that influence software piracy among students. 170 students who are involved and have conmiitted software piracy mere selected from various faculties in UiTM Shah Alam campus in order to participating in this survey. Statistical descriptive had been used in order to identify tasks performed with pirated software by students in UiTM. Correlation coefficient analyses result shows there is significant relationship between costs of original software, knowledge on computer software copyright laws, intention to use pirated software and attitudes towards software piracy. Crosstabulation analysis indicates that only student's computer ownership is not significant with their intention to use pirated software.